HYSTEROSALPINGOGRAPHY - Dimitrovska, Maja Jakimovska; Jovanovska, Elizabeta Stojovska; Nedelkoski, Martin; Jakimovski, Dragan (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
To emphasize the role and value of hysterosalpingography (HSG) as a radiological procedure for investigation of the uterine cavity and the patency of the fallopian tubes. This is a retrospective study of a group of 43 patients with infertility examined at the University institute of radiology in Skopje, Republic of North Macedonia during a two months period in 2025. The HSG was part of the infertility examination, evaluation and treatment at the University clinic of gynecology and obstetrics in Skopje, Republic of North Macedonia. The mean age of the 43 patients included in the study was 34.02 years with a range of 20 to 47 years. Most of the participants, 27 (62.8%) had primary infertility. The period of infertility duration was under 5 years in 31 (72.1%) of the women. Hysterosalpingograms showed normal uterine morphology in 31(72.1%) of the included patients, tubal morphology was normal in 35 (81.4%) of the patients, while 42 (97.7%) of the 43 participants had normal cervical findings.   The most prevalent uterine anomaly was the arcuate uterus present in 6 (13.9%) of the patients, while the rarest findings were the hypoplastic and the unicornuate uterus, each presenting in only 1 (2.3%) of the patients. Cervical insufficiency was detected in 15 (34.9%) of the patients. Patent tubal dilatation and hydrosalpinx were the most common tubal abnormalities, each finding appearing in 3 (7%) of the patients. Normal tubal patency was present in 36 (83.7%) of the included women, while 3 (7%) of the patients had bilateral tubal occlusion. HSG is a method of choice for demonstration of the uterine endometrial contour, filling of the fallopian tubes and intraperitoneal spillage of contrast with the purpose of establishing tubal patency. Key words: Hysterosalpingography, female infertility, Fallopian tubes.